Shifting, overlapping and expanding use of "precision oncology" terminology: a retrospective literature analysis. Issue 6 (7th June 2020) - Tran, Audrey; Klossner, Quiana; Crain, Tyler; Prasad, Vinay
Abstract : Importance: The terms "personalized oncology" and "precision oncology" have increased in usage and have generated considerable traction in terms of public attention and research funding. To our knowledge, no prior study has as thoroughly documented the use of the "precision oncology" terminology over the last decade. Objective: To determine how the use of the terms "personalized oncology" and "precision oncology" have changed over time. Design: A retrospective literature analysis using two databases (PubMed and Scopus) over 10 years was performed. Manuscripts using either term "personalized oncology" or "precision oncology" were collected. Manuscripts published in 2011, 2013, 2015, 2017 and through 30 June 2019 were pulled for text analysis. Common reasons for exclusion were if the search term appeared in the institution name only, the search term appeared only in keyword or publication title, or the search term was used to justify the relevance or application of research with no clear definition. Setting: Manuscripts published and catalogued in PubMed or Scopus. Results: In our study, we analysed 399 unique manuscripts published over the last decade. Over time, the terminology has shifted from "personalized oncology" to "precision oncology". Targeted therapy, molecular biomarker-guided tumour profiling and next generation sequencing (ie, "omics-guided tumor profiling") are the three most common definitions of the term. While these definitions are somewhat overlapping in concept, over the decade we observed an increase in the number of distinct interpretations of "precision oncology", ranging from structural biology to clinical practice. Conclusions and relevance: We have observed that the phrase "precision oncology" is shifting, overlapping and expanding in definition. This all-encompassing approach to defining "precision oncology" ironically renders the term imprecise. Our analysis highlights the inherent challenges in defining novel movements in medicine.